Comparative Study on The Nutrient Composition of The Exocarp And Other Parts of a Watermelon. - Luutu, Charles Lasto (Kabale University, 2024)
Many people eat the stripped watermelon variety most especially during the very hot days to quench their thirst. However, they eat only the endocarp and discard away the exocarp and seeds. The study investigated the nutrient content in the exocarp and endocarp of a watermelon. Two samples of watermelon were obtained and juice extracts were obtained from both the exocarp and idoearp. The solution extracts were tested with iodine solution for starch, Benedict's solution for reducing sugars, and DCPIP for Vitamin C. Further, the concentration of Vitamin C and reducing sugars was determined quantitatively by redox titration. The study found out that the endocarp had high levels of carbohydrate concentration, and both the exocarp and endocarp had reducing sugars and Vitamin C, on qualitative analysis, the exocarp had higher concentrations of Vitamin C than the endocarp of a watermelon. Furthermore, the endocarp had a higher concentration of reducing sugars than the exocarp of a watermelon.